ANALISIS PENGELOLAAN DAN PERANAN ALOKASI DANA DESA (ADD) BAGI PENINGKATAN KESEJAHTERAAN MASYARAKAT - Nuwun Priyono (JURNAL AKUNTANSI, 2022)
ABSTRACTThe purpose of this study was to determine the management of ADD, supporting factors, inhibiting factors for ADD management and the role of ADD for improving community welfare in Dawung Village, Tegalrejo District, Magelang Regency in 2018-2019. ADD management includes planning, implementation, administration, reporting and accountability. This study uses a qualitative approach with a descriptive method. The data validity technique used is a triangulation technique with sources. The data used are data sourced from interviews, documentation, and literature studies. The results showed that in the management of ADD, at the implementation, administration, and reporting stages, it was in accordance with Permendagri No. 20 of 2018. While in the planning stage of the 4 indicators of conformity to planning, there is 1 indicator that is not appropriate. Then in the accountability stage of the 3 conformity indicators, there is 1 indicator that is not appropriate. Supporting factors for ADD management are budget transparency, financial management team performance, participation, and the existence of Siskeudes. Meanwhile, the inhibiting factors for ADD management are changes in the report format, delays in ADD disbursement, regulatory delays, Human Resources, and the lack of Siskeudes training. The role of ADD includes increasing the distribution of various aspects of income in rural communities, increasing and encouraging work and business opportunities for the community, as well as being able to encourage increased self-reliance and community participation in village development.Keywords: village fund allocation (add); management; role.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengelolaan ADD, faktor pendukung, faktor penghambat pengelolaan ADD serta peranan ADD bagi peningkatan kesejahteraan masyarakat di Desa Dawung Kecamatan Tegalrejo Kabupaten Magelang pada tahun 2018-2019. Pengelolaan ADD meliputi perencanaan, pelaksanaan, penatausahaan, pelaporan serta pertanggungjawaban. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik keabsahan data yang digunakan adalah teknik triangulasi dengan sumber. Data yang digunakan adalah data yang bersumber dari wawancara, dokumentasi, serta studi kepustakaan. Hasil penelitian menunjukkan bahwa dalam pengelolaan ADD, pada tahap pelaksanaan, penatausahaan, dan pelaporan telah sesuai dengan Permendagri No. 20 Tahun 2018. Sedangkan dalam tahap perencanaan dari 4 indikator kesesuaian dengan perencanaan, terdapat 1 indikator tidak sesuai. Kemudian dalam tahap pertanggungjawaban dari 3 indikator kesesuaian terdapat 1 indikator yang tidak sesuai. Faktor pendukung pengelolaan ADD yaitu transparansi anggaran, kinerja tim pengelola keuangan, partisipasi, dan adanya Siskeudes. Sedangkan faktor penghambat pengelolaan ADD yaitu perubahan format laporan, keterlambatan pencairan ADD, keterlambatan regulasi, Sumber Daya Manusia, dan Masih minimnya pelatihan Siskeudes. Peranan ADD meliputi meningkatkan pemerataan berbagai aspek pendapatan yang ada pada masyarakat desa, meningkatkan dan mendorong kesempatan bekerja dan berusaha bagi masyarakat, serta dapat mendorong dalam peningkatan swadaya dan partisipasi masyarakat dalam pembangunan desa. Kata Kunci: alokasi dana desa (add); pengelolaan; peranan.